Molecular cytogenetic insights to the phylogenetic affinities of the giraffe (Giraffa camelopardalis) and pronghorn (Antilocapra americana) - Cernohorska, Halina; Kubickova, Svatava; Kopecna, Olga; Kulemzina, Anastasia I; Perelman, Polina L; Elder, Frederick F B; Robinson, Terence J; Graphodatsky, Alexander S; Rubes, Jiri (Chromosome research, 2013)
Five families are traditionally recognized within higher ruminants (Pecora): Bovidae, Moschidae, Cervidae, Giraffidae and Antilocapridae. The phylogenetic relationships of Antilocapridae and Giraffidae within Pecora are, however, uncertain. While numerous fusions (mostly Robertsonian) have accumulated in the giraffe's karyotype (Giraffa camelopardalis, Giraffidae, 2n = 30), that of the pronghorn (Antilocapra americana, Antilocapridae, 2n = 58) is very similar to the hypothesised pecoran ancestral state (2n = 58). We examined the chromosomal rearrangements of two species, the giraffe and pronghorn, using a combination of fluorescence in situ hybridization painting probes and BAC clones derived from cattle (Bos taurus, Bovidae). Our data place Moschus (Moschidae) closer to Bovidae than Cervidae. Although the alternative (i.e., Moschidae + Cervidae as sister groups) could not be discounted in recent sequence-based analyses, cytogenetics bolsters conclusions that the former is more likely. Additionally, DNA sequences were isolated from the centromeric regions of both species and compared. Analysis of cenDNA show that unlike the pronghorn, the centromeres of the giraffe are probably organized in a more complex fashion comprising different repetitive sequences specific to single chromosomal pairs or groups of chromosomes. The distribution of nucleolar organiser region (NOR) sites, often an effective phylogenetic marker, were also examined in the two species. In the giraffe, the position of NORs seems to be autapomorphic since similar localizations have not been found in other species within Pecora.
Keywords: Cattle; centromera; hybridizace in situ fluorescenční; fylogeneze; Chromosome Painting; Centromere; skot; Phylogeny; Repetitive Sequences, Nucleic Acid; karyotyp; Nucleolus Organizer Region; translokace genetická; chromozom X; savčí chromozomy; Chromosome Banding; X Chromosome; Animals; Ruminants; Chromosomes, Mammalian; organizátor jadérka; zvířata; pruhování chromozomů; Translocation, Genetic; repetitivní sekvence nukleových kyselin; In Situ Hybridization, Fluorescence; Karyotype; přežvýkavci; malování chromozomů